Alterations in rat prefrontal cortex kynurenic acid levels are involved in the enduring cognitive dysfunctions induced by tetrahydrocannabinol exposure during the adolescence - Beggiato, Sarah; Ieraci, Alessandro; Zuccarini, Mariachiara; Di Iorio, Patrizia; Schwarcz, Robert; Ferraro, Luca (Frontiers in Psychiatry, 2022)
Cannabis abuse during adolescence is a risk factor for cognitive impairments in psychiatric disorders later in life. To date, the possible causal relationship between cannabinoids, kynurenic acid (KYNA; i.e. a neuroactive metabolite of tryptophan degradation) and cognition has not been investigated in adolescence. Early exposure to Δ9-tetrahydrocannabinol (THC; i.e. the main psychotropic component of cannabis) causes enduring cognitive deficits, which critically involve impaired glutamatergic function in the prefrontal cortex (PFC). In addition, prenatal cannabis exposure results in enduring increases in PFC KYNA levels. Based on these findings, the effects of chronic THC exposure in rats, during another critical period of neurodevelopment particularly sensitive to perturbation by exogenous stimuli, such as adolescence, have been investigated. Male Wistar rats were chronically treated with vehicle or ascending intraperitoneal (i.p.) doses of THC starting on postnatal day (PND) 35 until PND 45. In adulthood (PND-75), cognitive assessment (Y-maze) and extracellular KYNA/glutamate levels were measured in the PFC by in vivo microdialysis, before and after a challenge with KYN (5 mg/kg i.p., the biological precursor of KYNA). By using the selective, brain-penetrable KAT II inhibitor PF-04859989, we then examined whether blockade of KYNA neosynthesis prevents the cognitive impairment. Compared to vehicle-treated controls, extracellular basal KYNA levels were higher in the PFC of adult rats chronically exposed to THC in adolescence (p<0.01). No changes were observed in extracellular glutamate levels. Following a challenge with KYN, extracellular KYNA levels similarly increased in both groups (i.e. vehicle- and THC-treated; p<0.001 and p<0.01 respectively). Chronic adolescent THC exposure negatively affected short-term memory (reduced spontaneous alternation), in adult animals (p<0.001), while PF-04859989 (30 mg/kg i.p.) restored the cognitive impairment (p<0.05). We propose that the observed alterations in PFC KYNA signalling might be involved in the cognitive dysfunction induced by the exposure to THC during the adolescence. In the translational realm, these experiments raise the prospect of prevention of KYNA neosynthesis as a possible novel approach to counteract some of the detrimental long-term effects of adolescence cannabis use.